THE ANIMAL AT THE PERSON'S SIDE AT THE END OF LIFE AND AFTER DEATH - QUESNE, Aloïse (MEDECINE LEGALE DROIT MEDICAL, 2025)
Animal, the presence of which helps to reduce pain and anxiety, has made its way into palliative care units in recent years. Although there is no legal framework, animal mediation and the visit of pets in extremis are proving to be a precious comfort for patients during this delicate period before death. In general, our attachment to animals is particularly strong: 68% of cat and dog owners surveyed consider their pet to be a fully-fledged member of the family, and 7 out of 10 French people say they are in favour of adopting a law allowing them to be buried with their pet. The study also looks at the post-mortem presence of animals, with the aim of being able to share their final resting place with their pet, so that this indestructible link can continue beyond death.